A clinicopathological study of interface dermatitis - Vijaya Kumar Hegde; Urmila N Khadilkar (Wolters Kluwer Medknow Publications, 2014)
Background: Interface dermatitis (ID) refers to a pattern of skin reaction characterized by an inflammatory infiltrate that appears to obscure the dermo-epidermal junction when observed at low power examination and referred to as lichenoid tissue reaction. A wide range of inflammatory skin diseases exhibits interface change with considerable overlap of histological features. The aim of the present study was to study the clinical features and microscopic features of ID. Materials and Methods: The material for the present study consisted of skin biopsy samples collected from patients attending the outpatient Department of Dermatology. The study was conducted for a period of 3 years from 2007 to 2010. During this period, a total of 125 cases was studied. Results: In the present study, a total of 125 cases of ID was studied which presented clinically as papulosquamous disorders. Majority of the cases of ID were seen in women (57.6%). Majority of ID were lichen planus (LP) and its variants (63.2%). Clinicopathological concordance was seen in 109 cases (87.2%) and discordance in 16 cases (12.8%). Conclusion: The mere presence of an interface lichenoid inflammatory reaction should not be the sole criterion for the diagnosis of LP or one of its many variants, as now seems to be the case. A clinicopathologic correlation is absolutely essential for a conclusive diagnosis of ID.